Routes of postoperative analgesia administration in surgical wards: practice vs. guidelines and economic implications - Bojic, Suzana; Ladjevic, Nebojsa; Palibrk, Ivan; Rancic, Nemanja; Bezmarevic, Mihailo; Meissner, Winfried; Zaslansky, Ruth; Stamer, Ulrike M.; Baumbach, Philipp; Stamenkovic, Dusica (Frontiers in Medicine, 2025)
IntroductionMultimodal analgesia, critical to postoperative recovery, typically involves oral (PO), intravenous (IV), or regional analgesia. The PO route is preferred for its non-invasive nature, cost-effectiveness, and comparable efficacy to parenteral routes. This study assessed whether analgesic practices in surgical wards align with current guidelines and evaluated the economic impact of deviations.Materials and methodsData from 2,354 adult patients, collected using the PAIN OUT methodology across 10 Serbian hospitals, were analyzed. Patients undergoing various surgeries were observed during the first 24 h postoperatively. We analyzed analgesic administration routes on surgical wards for the entire cohort and a subgroup where PO administration was deemed feasible. Potential savings of transitioning from parenteral to PO were calculated, including medication, disposables, and labor costs.ResultsIn the entire cohort, the IV route was used in 86% of patients receiving non-opioids and 39% receiving opioids, while the IM route was used in 7 and 4%, respectively. The PO route was employed in only 1% of patients. Among 1,850 patients for whom the PO route was considered feasible, the IV route was used in 86% for non-opioids and 38% for opioids, and the IM route in 8 and 5%, respectively. Transitioning from parenteral to PO administration would reduce costs from 822.3 RSD (7.84 USD) to 124.5 RSD (1.19 USD) per patient, resulting in 85% savings.ConclusionThe reliance on IV analgesia and underuse of PO route in Serbia reveals a gap between practice and guidelines. Transitioning to PO analgesia could result in significant cost savings.